A model for evaluating academic research centers: Case study of the Asian/Pacific Islander Youth Violence Prevention Center. (February 2018) - Nishimura, Stephanie T.; Hishinuma, Earl S.; Goebert, Deborah A.; Onoye, Jane M.M.; Sugimoto-Matsuda, Jeanelle J.
Highlights: Research centers serve a very important purpose to advance science and research. Minimal research has been done on comprehensive evaluations of research centers. A case study of the evaluation of one research center is provided. Positive outcomes and lessons learned are discussed. It is important to systematically evaluate research centers. Abstract: Objectives: To provide one model for evaluating academic research centers, given their vital role in addressing public health issues. Methods: A theoretical framework is described for a comprehensive evaluation plan for research centers. This framework is applied to one specific center by describing the center's Logic Model and Evaluation Plan, including a sample of the center's activities. Results: Formative and summative evaluation information is summarized. In addition, a summary of outcomes is provided: improved practice and policy; reduction of risk factors and increase in protective factors; reduction of interpersonal youth violence in the community; and national prototype for prevention of interpersonal youth violence. Conclusions: Research centers are important mechanisms to advance science and improve people's quality of life. Because of their more infrastructure-intensive and comprehensive approach, they also require substantial resources for success, and thus, also require careful accountability. It is therefore important to comprehensively evaluate these centers. As provided herein, a more systematic and structured approach utilizing logic models, an evaluation plan, and successful processes can provide research centers with a functionally useful method in their evaluation.